2008
DOI: 10.1152/ajpregu.00899.2007
|View full text |Cite
|
Sign up to set email alerts
|

C2 spinal cord stimulation induces dynorphin release from rat T4 spinal cord: potential modulation of myocardial ischemia-sensitive neurons

Abstract: Ding XH, Hua F, Sutherly K, Ardell JL, Williams CA. C2 spinal cord stimulation induces dynorphin release from rat T4 spinal cord: potential modulation of myocardial ischemia-sensitive neurons. Am J Physiol Regul Integr Comp Physiol 295: R1519 -R1528, 2008. First published August 27, 2008 doi:10.1152/ajpregu.00899.2007.-During myocardial ischemia, the cranial cervical spinal cord (C1-C2) modulates the central processing of the cardiac nociceptive signal. This study was done to determine 1) whether C2 SCS-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…In animal models of reduced coronary reserve, SCS mitigates the ST segment deviations associated with chemical activation of intrathoracic adrenergic neurons (14). SCS by itself (18), or in combination with coronary artery occlusion (17), increases cFos expression within subpopula- . C: dots in the raster sweep plot represent action potentials generated by 4 neurons recorded during the 1,792 cardiac cycles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In animal models of reduced coronary reserve, SCS mitigates the ST segment deviations associated with chemical activation of intrathoracic adrenergic neurons (14). SCS by itself (18), or in combination with coronary artery occlusion (17), increases cFos expression within subpopula- . C: dots in the raster sweep plot represent action potentials generated by 4 neurons recorded during the 1,792 cardiac cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Electrical neuromodulation impacts on the dynamic interactions among autonomic afferent and efferent neurons mediated via, as yet poorly defined, spinal cord and peripheral neural circuits (18,20,35,43). Centrally, SCS reduces the release of neuropeptides from cardiac nociceptive afferent neurons (17), reduces intrasegmental and supraspinal transmission of cardiac nociceptive information (20,35), and increases the activity of a subpopulation of thoracic sympathetic preganglionic efferent neurons (17,18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Research for the underlying mechanisms has largely concentrated on the balance between myocardial oxygen consumption and oxygen supply after SCS, but recent experimental and clinical studies failed to detect an increase in local flow or a redistribution of myocardial blood flow following SCS [11,12]. Although the specific neurotransmitters that modulated by SCS remain poorly elucidated, available data showed that SCS could induce endogenous opioids release from cardiac sympathetic afferent nerve terminals [13,14]. Moreover, recent studies have shown that continuous opioid receptor activation…”
Section: R Eperfusion Of the Ischaemic Bed-at-risk Was The Basismentioning
confidence: 99%
“…At the spinal cord itself, SCS induces the release of neuromodulators such as dynorphin, blunts the release of primary afferent related neurotransmitters such as substance P, and alters activity with sympathetic preganglionic neurons contained within the intermediolateral cell column 68, 69 . As such it thereby alters ascending signals to higher centers 15, 57, 58 and alters autonomic efferent outflows to peripheral aspects of the cardiac nervous system.…”
Section: Introductionmentioning
confidence: 99%